2016
DOI: 10.14238/pi46.3.2006.113-7
|View full text |Cite
|
Sign up to set email alerts
|

The value of IgG to IgM ratio in predicting secondary dengue infection

Abstract: Background The determination of primary or secondary dengueinfection using hemagglutination inhibition (HI) test is time-con-suming. The IgG to IgM ratio which can be obtained earlier wasused by several studies to differentiate secondary from primaryinfection, but they still reported various cut-off points.Objective To find the diagnostic value and best cut off point ofIgG to IgM ratio for predicting secondary dengue infection.Methods This was a prospective study carried out between July2003 and June 2004. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…A study using samples from IgM and IgG titer-negative sera found a cut off IgM/IgG OD ratio that was comparable with studies previously [ 9 , 24 ]. This study also used samples from IgM and IgG titer-negative sera and also found a cut off IgG/IgM ratio comparable to a study previously [ 23 ].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…A study using samples from IgM and IgG titer-negative sera found a cut off IgM/IgG OD ratio that was comparable with studies previously [ 9 , 24 ]. This study also used samples from IgM and IgG titer-negative sera and also found a cut off IgG/IgM ratio comparable to a study previously [ 23 ].…”
Section: Discussionsupporting
confidence: 73%
“…A study in Bali, Indonesia found IgG/IgM ratio of ≥ 1.1 on the day 5–7 of disease is a good predictor of secondary dengue infection. This study was done on children hospitalized for suspected DENV infection, with mean age of 6 year-old [ 23 ]. Study in Thailand using HI test as the gold standard found that the best cut off point of IgG/IgM ratio for secondary infection was ≥ 1.78 [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation